2015
DOI: 10.1074/jbc.m114.593962
|View full text |Cite
|
Sign up to set email alerts
|

The Ether Lipid Precursor Hexadecylglycerol Stimulates the Release and Changes the Composition of Exosomes Derived from PC-3 Cells

Abstract: Background: Lipids are emerging as important constituents of the molecular machinery involved in the formation and release of exosomes. Results: The ether lipid precursor hexadecylglycerol stimulates the release and changes the composition of exosomes. Conclusion: Ether lipids are important modulators of exosome release. Significance: By knowing the machinery involved in exosome release, it would be possible to modulate this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 53 publications
6
81
0
Order By: Relevance
“…Interestingly, Phuyal et al recently reported that the ether lipid precursor hexadecylglycerol added to PC-3 cells doubled the cellular levels of ether lipids in the cells, with increased levels of ether lipids also observed in their exosomes. Furthermore, cells containing high levels of ether lipids were found to release more exosomes than control cells [57]. To date however, the possible functional role of ether lipids in exosome mediated intercellular signaling have not yet been explored.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Phuyal et al recently reported that the ether lipid precursor hexadecylglycerol added to PC-3 cells doubled the cellular levels of ether lipids in the cells, with increased levels of ether lipids also observed in their exosomes. Furthermore, cells containing high levels of ether lipids were found to release more exosomes than control cells [57]. To date however, the possible functional role of ether lipids in exosome mediated intercellular signaling have not yet been explored.…”
Section: Resultsmentioning
confidence: 99%
“…Several articles had shown that different exosomes derived from a variety of cells contained different components, for example heat shock proteins, annexin, lipids, and so on [2830]. Phuyal S et al had reported that an increase in cellular ether lipids (including PCs) was associated with changes in the release and composition of exosomes in PC-3 cells [31]. The ePCs belong to subclasses of PCs, and ePCs activate Pl-3-kinase and may participate in mitogenic responses [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although their precise role in cancer pathogenicity is unclear, ether lipids are important for the organization of detergent-resistant membrane microdomains [2]. Ether lipids may also be required for the assembly and release of exosomes, 40–100-nm vesicles secreted by cells, which may be involved in cell–cell communication and promoting cancer metastasis [67]. …”
Section: Peroxisomal Dysfunction In Disease Developmentmentioning
confidence: 99%